2004
DOI: 10.1097/00001756-200408260-00025
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid responsive genes during neuronal differentiation of embryonic stem cells

Abstract: Ascorbic acid has been reported to enhance differentiation of embryonic stem (ES) cells into neurons, however, the specific functions of ascorbic acid have not been defined yet. To address this issue, gene expression profiling was performed using cDNA microarray. Ascorbic acid increased the expressions of genes involved in neurogenesis, maturation, and neurotransmission. Furthermore, statistical analysis using Fisher's exact test revealed ascorbic acid significantly modulated the genes involved in cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 24 publications
5
43
0
Order By: Relevance
“…Previous reports showed that ascorbic acid can influence proliferation and differentiation of CNS progenitor cells both in vivo and in vitro [27,32,42,55,70]. Our data appear to be consistent with these reports.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports showed that ascorbic acid can influence proliferation and differentiation of CNS progenitor cells both in vivo and in vitro [27,32,42,55,70]. Our data appear to be consistent with these reports.…”
Section: Discussionsupporting
confidence: 93%
“…An aliquot of RNA (500 ng) was reverse-transcribed into cDNA by oligo(dT) [12][13][14][15][16][17][18] primer. Real time PCR contained 100 ng of template cDNA, 1ϫ SYBR GREEN master mix (Qiagen), and 100 nM specific forward and reverse primers in a 25-l volume of reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18vincing evidence that AA also influences differentiation of other cell type lineages, such as neuronal cells, that produce little or no matrix (16). Furthermore, the gulonolactone oxidase knock-out mice have normal levels of proline hydroxylation and collagen production in the tail, mammary gland, and tumors, whereas these mice show widespread abnormalities in multiple organs besides the bone (2,17).…”
mentioning
confidence: 87%
“…[36][37][38] AsA has been reported to induce differentiation of embryonic cortical precursors and midbrain neuroblasts into neurons and to alter gene expression involved in neurogenesis, maturation, and neurotransmission. [39][40][41][42] Our present study indicates the possibility that AsA may regulate the redox state in the neural cells and play a crucial role in the differentiation and development of the brain. However, mechanism of neuronal differentiation regulated by AsA is not yet clear.…”
Section: Discussionmentioning
confidence: 53%